Customary Intervention in Marriage Prohibition: A Study of the Prohibition of Abstinence Marriages in Nagari Singkarak and Nagari Saniangbaka, X Koto Singkarak Subdistrict - Nabila, Dila; Eficandra, Eficandra; Zulkifli, Zulkifli (JISRAH: Jurnal Integrasi Ilmu Syariah, 2024)
The main problems in this study are the background of the ban on matrimony and the public's views on the ban and the impact of a ban on marriage between the children of Nagari Singkarak and Nagari Saniangbaka in the Prespective of Islamic Law. The purpose of this research is to know and understand the background and public view of the Ban on Marriage and the Impact of a Ban on Matrimony between Nagari singkarak's children and the Prespektive of the Law of Islam. The type of research used is field research with the method used is a qualitative approach. The primary sources of data in this study are local scholars, perpetrators who violated the prohibition of marriage and who cancelled marriage, Niniak mamak party who violates the prohibited marriages, Civil Rights of Nagari (KAN), Wali Nagari Singkarak and Saniangbaka, Parents/Families who violate the forbidden marriage. The data collection technique used in this study is the interview. The data analysis technique in this research is the reduction of data, the display of data and conclusions or conclusions. This research found results that first, the background of the occurrence of the ban on marriage suspension between Nagari Singkarak and Nagari Saniangbaka's children because of the oath of the ancestors that they said they had a brotherly relationship because of an oath that was set so that they could not make marriage. In the case of a marriage ban, there are two reasons why people accept the rule of the ban because they believe in the absolute provisions of the ancestral oath that they are brothers and sisters so that marriage is not permitted. Some people do not accept this ban because it is contrary to Islamic law. Second, the effect of this ban is two, namely: a. the cancellation of marriage due to the ban on marriage. b. the existence of a series marriage carried out by the community because it did not get permission from the people, the elders and the government. Seeing from the perspective of Islamic law, this prohibition of marriage is more harmful than beneficial, so it can cause forbidden acts.